Phytosociological studies of the forests with sessile oak and Norway spruce from South-Eastern Transylvania - Indreica, Adrian; Kelemen, Mihai (Annals of Forest Research, 2011)
The forests with sessile oak (Quercus petraea) and Norway spruce (Picea abies) from south-eastern Transylvania represent a peculiar type of phytocenoses, rather unusual for the present-day vegetation of Romania’s territory. Aim of the study is to provide a detailed description of the vegetation and to identify the phytosociological and typological units to which it could belong. Beside this, stand structure and regeneration status of the main tree species are illustrated. The studied area is located around Carpathian intermountain depressions Braşov and Ciuc, where vegetation had a peculiar history and today sessile oak forests on high altitude exists, interfering with spruce forests. The hypothesis of the process naturalness is supported by vegetation history in the area, climate, stand structure and peculiarities of herb layer composition (the mixture of relic of both mountain-boreal origin and south-European origin, like Vaccinium vitisidaea, Pyrola rotundifolia and respectively Potentilla micrantha, Lathyrus venetus respectively. Sintaxonomically, studied phytocenoses with sessile oak and spruce belong mainly to acidophilus oak forests (Luzulo luzuloidis-Quercetum petraeae), but some of them resemble oak-hornbeam forests (Carici pilosae-Carpinetum), indicating a more recent change in stand structure and suggesting that not the soil, but the climate is the driving force of succession. Regeneration of sessile oak is at least satisfactory, but the expansion of spruce in such stands could seriously restrict the survival of sessile oak. A new typological unit will be appropriate, for a better management of sessile oak forests with spruce admixture.
Keywords: sessile oak – spruce forests; phytosociology; vegetation succesion